Mathematical model of distal radius orientation - Chen, Cheng-Kuang; Wu, Tai-Yin; Liao, Yu-Ciao; Fuh, Chiou-Shann; Chen, Kuan-Hao; Weng, Pei-Wei; Wang, Jr-Yi; Chen, Chih-Yu; Huang, Yu-Min; Chen, Chung-Pei; Chu, Yo-Lun; Yeh, Kuei-Lin; et al. (Frontiers in Surgery, 2022)
Distal radius orientation is important in evaluating Colles’ fracture. In most cases, the wrist was protected by bandage, splint, or cast. Therefore, it was difficult for the radiology technician to take perfect antero-posterior (AP) and lateral (LAT) view radiographs. In this study, we build a mathematical model and calculate the pronation angle needed to produce dorsal tilt, which is volar tilt in perfect lateral view radiograph. The formulas are all incorporated into Excel to facilitate usage.